2005
DOI: 10.1002/jbm.a.30530
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and degradation of aliphatic segmented poly(ester amide)s: In vitro and in vivo evaluation

Abstract: Aliphatic segmented poly(ester amide)s, comprising a crystallizable amide phase and a flexible amorphous ester phase, were investigated for potential use in biomedical applications. By varying the amide content and the type of crystallizable amide segments, the polymer's thermal and mechanical properties can readily be tuned. Polymers with 25 and 50 mol % of amide content are noncytotoxic and sustain growth of fibroblasts onto polymer films. The in vitro degradation of these polymers was followed in PBS (pH 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 19 publications
4
23
0
Order By: Relevance
“…Whereas the use of PEAs derived from non-amino acid precursors have been studied as cell supporting biomaterials [11,43,44,45] the attachment and spreading behavior of cells on PEAs derived from α−amino acids is notably absent from the literature. In fact our study is only preceded by two previous studies on glycine [31] and l -alanine [20] containing PEAs where it was shown both PEAs to be less favorable to cells.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the use of PEAs derived from non-amino acid precursors have been studied as cell supporting biomaterials [11,43,44,45] the attachment and spreading behavior of cells on PEAs derived from α−amino acids is notably absent from the literature. In fact our study is only preceded by two previous studies on glycine [31] and l -alanine [20] containing PEAs where it was shown both PEAs to be less favorable to cells.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of subcutaneously implanted devices, their size, shape, mechanical properties, type of biomaterial, implantation duration and even method of implantation can yield a different response. The FBR can be minimized by using materials with mechanical properties similar to those of the surrounding tissue [13][14][15], by incorporating hydrophilic coatings that prevent protein adsorption (biofouling) [16][17][18][19][20] and by using biocompatible materials that do not produce toxic or irritating by-products upon degradation [21][22][23][24]. However, these approaches only minimize the FBR but do not eliminate it altogether.…”
Section: Introductionmentioning
confidence: 99%
“…Lips et al investigated aliphatic segmented PEAs, comprising a crystallizable amide phase and a flexible amorphous ester phase for potential use in biomedical applications 48. By varying the amide content and the type of crystallizable amide segments, the polymer's thermal and mechanical properties can readily be tuned.…”
Section: Biocompatibilitymentioning
confidence: 99%